Cured shield waste clay and preparation method thereof
By mixing waste clay with a variety of curing agents and additives to form an efficient curing system, the problems of low soil curing strength and conversion of waste soil treatment into reuse resources are solved, and efficient curing and performance improvement are achieved.
Patent Information
- Application Number
- CN202510040350.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-11
AI Technical Summary
The problem of soil solidification strength in the prior art is low, and how to convert large-scale shield waste soil treatment into reuse resources has not been effectively solved.
A highly efficient curing system is formed by mixing and activating waste clay with composite additives composed of magnesium oxide, calcium carbide slag, boron mud, modified sisal fiber, biological enzyme-concave and concave rod soil and anionic surfactant.
It has achieved efficient curing of high-plastic and high-water content waste clay, significantly improved the strength, water stability and crack resistance of the cured soil, met the requirements of highway base filling, and realized the reuse of resources.
Smart Images

Figure CN119797870A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soil solidification, and in particular to solidified shield waste clay and a preparation method thereof. Background Art
[0002] At present, the traditional open-air stacking or landfilling methods are still used in tunnel projects to deal with the waste soil generated by construction. These treatment methods will not only cause waste of resources, but improper treatment will also cause a series of environmental problems such as soil compaction and river siltation, and even pose a serious safety threat to the surrounding environment and residents. With the continuous excavation of the shield machine, a large amount of dehydrated waste clay will be generated at the construction site every day. Therefore, the engineering community is paying more and more attention to the treatment efficiency of the dehydrated waste clay generated by the slurry shield project with clay strata as the main component. Therefore, these shield waste soils are a potential resource. my country's large-scale engineering construction still needs a large amount of high-quality soil for filling, sea reclamation and island construction. The rational, efficient and safe use of shield waste soil can not only turn waste into treasure, but also avoid the occurrence of excessive excavation of cultivated land, mountain quarrying and other phenomena. Therefore, how to safely, efficiently and environmentally friendly convert large-scale shield waste soil into reusable resources is a problem that the engineering community is currently concerned about.
[0003] The existing patent CN201911328851.8 discloses an inorganic composite curing agent suitable for soil in coastal areas and its preparation method. The inorganic composite curing agent is composed of 85%-95% main curing agent and 5%-15% admixture by mass percentage; wherein the main curing agent is composed of 30%-70% cement and 30%-70% lime; the admixture is composed of 20%-40% polyaluminium chloride, 20%-40% polyferric chloride, 10%-30% active magnesium oxide, 10%-30% calcium sulfate, 5%-30% calcium chloride and 5%-30% calcium carbonate. During the preparation, each component is weighed in proportion, and mixed evenly to obtain the main curing agent and the admixture, and then the main curing agent and the admixture are mixed evenly in proportion to obtain the inorganic composite curing agent. The inorganic composite curing agent is used to solidify soil in coastal areas, promote the solidification of silt, clay, silt and silty soil in coastal areas, and can effectively improve the compressive strength, water stability and crack resistance of soil in coastal areas. However, the above curing agents are all inorganic materials, which are relatively single and mostly concentrated in cement and lime, limiting their potential in improving soil structure and performance. Cement-cured clay is too expensive and has a short setting time, which is not conducive to on-site construction. The strength of lime-cured clay increases slowly, and a large amount is required to meet the roadbed strength requirements. Summary of the invention
[0004] In view of this, the present invention proposes a solidified shield waste clay and a preparation method thereof to solve the problems of low soil solidification strength in the prior art and how to convert large-scale shield waste soil into recyclable resources.
[0005] The technical solution of the present invention is achieved as follows: The present invention provides a solidified shield waste clay, which comprises the following components by weight: 1000 parts of waste clay, 20-80 parts of magnesium oxide, 40-100 parts of carbide slag, 60-80 parts of boric mud, 10-15 parts of composite additives and 2-3 parts of activator, wherein the composite additive is formed by compounding modified sisal fiber, bio-enzyme-attapulgite and anionic surfactant.
[0006] On the basis of the above technical scheme, preferably, magnesium oxide is produced in Haicheng, Liaoning, is light yellow in color, and is in the form of extremely fine powder, with an active ACC value of 75s; boron mud is alkaline, with a pH value of 8-10; and carbide slag is gray in color and has a fineness of 200 mesh.
[0007] In the present invention, the waste clay is generated when the shield passes through the clay layer. After being improved by mud, foaming agent, etc., it is discharged by the spiral discharger and is silty, with the characteristics of high liquid limit, high water content and low strength. Waste clay is used as the main raw material to provide basic materials. Its reuse not only solves the problem of waste disposal, but also reduces costs, which is in line with the concept of circular economy. Magnesium oxide, carbide slag and boron mud are used as main curing agents, wherein magnesium oxide reacts with water to generate magnesium hydroxide, forming a network structure, and enhancing the binding force between soil particles. The magnesium oxide in the present invention is active magnesium oxide. After the active magnesium oxide is placed in a CO2 environment for curing, it is found that the strength and stability of the abandoned clay solidified by the active magnesium oxide after carbonization are significantly improved, and part of the CO2 gas is also consumed. From the perspective of fossil energy consumption and CO2 gas emissions, the active magnesium oxide curing combined with carbonization technology is a more efficient and environmentally friendly curing method; carbide slag contains a large amount of calcium hydroxide, which can react with silicon dioxide and aluminum oxide in the soil to produce volcanic ash to generate cementitious calcium silicate hydrate and calcium aluminate hydrate, thereby enhancing the curing effect and improving the soil strength; the boron compounds in the boron mud can form a complex network structure with other components in the soil, thereby improving the density and impermeability of the soil.
[0008] On the basis of the above technical solution, preferably, the composite additive comprises 3-5 parts of modified sisal fiber, 5-8 parts of biological enzyme-attapulgite, and 2-3 parts of anionic surfactant.
[0009] The modified sisal fiber, bioenzyme-attapulgite and anionic surfactant form a composite additive as a secondary curing agent. The modified sisal fiber has high tensile strength and good dispersibility, and can form a three-dimensional network structure in the soil to improve the overall strength and crack resistance of the soil. The bioenzyme loaded on the attapulgite is released during the curing process, which can catalyze specific chemical reactions, such as urea hydrolysis, produce calcium carbonate precipitation, and enhance the bonding between soil particles. The anionic surfactant can form a hydrophobic film on the surface of soil particles, reduce the water absorption of the soil, and thus improve the water stability of the cured soil. The three-dimensional network structure formed by the modified sisal fiber provides a larger reaction surface area for the bioenzyme-attapulgite, while the anionic surfactant can improve the dispersibility of the attapulgite, so that the bioenzyme is more evenly distributed in the soil. At the same time, the hydrophobic film formed by the surfactant can protect the bioenzyme and prolong its activity time. In the composite additive, the modified sisal fiber provides physical reinforcement, the bioenzyme provides chemical curing, and the anionic surfactant improves hydrophobicity. The three work together to comprehensively improve the soil performance.
[0010] On the basis of the above technical solution, preferably, the preparation method of the modified sisal fiber comprises the following steps:
[0011] A1, placing the sisal fiber in deionized water for ultrasonic cleaning, and then immersing the sisal fiber in a NaOH solution for alkali treatment to obtain pretreated sisal fiber;
[0012] A2. The pretreated sisal fiber is mixed with deionized water, maleic anhydride solution is added, and then ammonium persulfate and anhydrous sodium sulfite are added, and the mixture is reacted at 80-100° C. for 2.5-3.5 hours to obtain modified sisal fiber.
[0013] Based on the above technical solution, preferably, in step A1, the mass percentage of the NaOH solution is 5-10%, and the alkali treatment time is 2-3h.
[0014] On the basis of the above technical solution, preferably, in step A2, the mass ratio of the pretreated sisal fiber, maleic anhydride, ammonium persulfate and anhydrous sodium sulfite is 100:5-10:1-2:0.5-1, and the maleic anhydride solution is a 10-20% maleic anhydride aqueous solution.
[0015] In step A1, impurities and pollutants on the surface of sisal fiber are removed by ultrasonic cleaning, and then the wax layer and some non-cellulose components on the surface of sisal fiber are removed by alkali treatment, so as to increase the specific surface area and roughness of the fiber and expose more hydroxyl groups. In step A2, maleic anhydride reacts with hydroxyl groups on cellulose molecules to introduce carboxyl groups on the surface of sisal fiber, which helps to improve the compatibility of modified fiber with inorganic components such as cement slurry and soil particles; sisal fiber and soil have a gripping force, and the disordered fiber network will produce spatial constraints on the soil, enhancing the overall strength of the soil. At the same time, maleic anhydride molecules contain double bonds, which can be connected to soil particles by ion coupling interaction / coordination or hydrogen bonding between minerals in waste clay, further solidifying, and it mainly acts on clay particles in the soil, reacting to expel adsorbed water in the soil.
[0016] On the basis of the above technical solution, preferably, the preparation method of the biological enzyme-attapulgite comprises the following steps:
[0017] S1, soaking the attapulgite in a 0.1-1.0M hydrochloric acid solution, and activating the reaction at 60-90°C for 2-4h to obtain pretreated attapulgite;
[0018] S2, placing the pretreated attapulgite in an ethanol aqueous solution, adding the modified solution to soak, stirring and reacting at 50-60° C. for 2-4 hours to obtain surface-modified attapulgite;
[0019] S3. Disperse the surface modified attapulgite in the biological enzyme solution, adsorb for 12-16 hours at 4-10°C to obtain the attapulgite loaded with biological enzymes, and then mix the attapulgite loaded with biological enzymes with carboxymethyl chitosan and gelatin, and let stand for 30-60 minutes to obtain biological enzyme-attapulgite.
[0020] On the basis of the above technical solution, preferably, in step S2, the modifying liquid is one or more of γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane, and the concentration of the modifying liquid is 2-5%.
[0021] Based on the above technical solution, preferably, in step S3, the concentration of the biological enzyme solution is 0.5-2%, and the mass ratio of attapulgite, carboxymethyl chitosan and gelatin loaded with the biological enzyme is 100:(5-15):(5-15); the biological enzyme is teranase and / or paenzyme.
[0022] In step S1, the cations between the attapulgite layers are replaced by acid treatment, the interlayer spacing is increased, and the activity and adsorption capacity of the attapulgite are improved. In step S2, the affinity of the attapulgite and the biological enzyme is further increased by the reaction of the silane coupling agent with the hydroxyl group on the surface of the attapulgite, and the fixation rate of the biological enzyme on the surface of the attapulgite is improved. In step S3, the modified attapulgite is loaded with biological enzymes through electrostatic adsorption, hydrogen bonding, etc., and the biological enzymes are coated with carboxymethyl chitosan and gelatin to avoid premature release of the biological enzymes when mixed with other components. During the curing process, the release of the biological enzymes coated in carboxymethyl chitosan and gelatin is triggered and controlled by an activator, and the compactness of the soil is further improved by the catalytic action of the biological enzymes.
[0023] On the basis of the above technical scheme, preferably, the activator is sodium bicarbonate or citric acid, the anionic surfactant is sodium sulfate of fatty alcohol polyoxyethylene ether and / or sodium lauryl sulfate, the plasticity index of the abandoned soil is 33, the moisture content is 41.73%, the clay content is about 14.3%, and the powder content is about 63.0%.
[0024] Sodium polyoxyethylene fatty alcohol ether sulfate and sodium lauryl sulfate have a hydrophilic head and a hydrophobic tail structure, which dissociate in water to provide a strong cationic charge. The cationic charge produces ionization exchange with soil particles in the soil structure. The hydrophilic head can combine with the cations adsorbed on the surface of clay particles through chemical chains, and the hydrophobic tail wraps the clay relay, destroying the capillary structure between soil particles and the bound water film on the clay surface, changing the hydrophilicity of the soil into hydrophobicity, thereby improving the soil solidification strength.
[0025] The present invention provides a method for preparing solidified shield waste clay, comprising the following steps:
[0026] (1) crushing and sieving the waste clay to less than 2 mm, and then uniformly mixing the waste clay powder, magnesium oxide, carbide slag and boron mud to obtain a mixture A;
[0027] (2) mixing the modified sisal fiber, the bio-enzyme-attapulgite and the anionic surfactant to obtain a composite additive;
[0028] (3) uniformly mixing the mixture A and the composite additive to obtain a mixture B;
[0029] (4) Add an activator to mixture B and stir evenly to obtain solidified shield waste clay.
[0030] Compared with the prior art, the solidified shield waste clay of the present invention has the following beneficial effects:
[0031] (1) The scheme for curing shield waste clay provided by the present invention realizes efficient curing and performance improvement of high plasticity and high water content waste clay through the synergistic effect of multiple components. This scheme not only solves the problem of waste clay treatment generated by shield construction, but also consumes soil moisture through the hydrolysis and hydration reaction of the inorganic soil curing agent itself and the volcanic ash reaction, thins the adsorbed water film, and produces adhesion to make the soil tighter; at the same time, the modified sisal fiber in the composite additive and the bio-enzyme attapulgite soil synergistically act to further strengthen the interaction between soil particles, and the anionic surfactant promotes the formation of more dense aggregates in the soil through the synergistic effect of ion exchange reaction and bio-enzyme, significantly improving the strength, water stability and crack resistance of the cured soil, providing a new technical path for the resource utilization of shield waste soil, and having significant environmental and economic benefits;
[0032] (2) The modified sisal fiber not only provides a physical reinforcement effect, but also achieves chemical bonding with attapulgite through the carboxyl groups introduced on the surface. The fiber surface modified with maleic anhydride can form ionic coupling or hydrogen bonding with minerals in the waste clay, and can also expel the adsorbed water in the soil, significantly improving the strength and stability of the solidified soil; anionic surfactants can further increase the density and anti-permeability of the soil;
[0033] (3) The efficient loading and intelligent release of bioenzymes were achieved by preparing bioenzyme-attapulgite. The surface of attapulgite was modified by silane coupling agent to increase the affinity with bioenzymes, while the coating of carboxymethyl chitosan and gelatin provided protection for the bioenzymes. Combined with the use of activators, the controlled release of bioenzymes during the curing process was achieved, which prolonged the action time of the enzymes and improved the curing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 The present invention is a flow chart for preparing solidified shield waste clay. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.
[0038] Magnesium oxide is produced in Haicheng, Liaoning Province. It is light yellow in color and in the form of extremely fine powder. Its active ACC value is 75s. The plasticity index of the waste soil is 33, and the moisture content is 41.73%. It is soft and difficult to compact. The clay content is about 14.3%, and the powder content is about 63.0%. The color of calcium carbide slag is gray, and the fineness is 200 mesh. The color of sisal fiber is light yellow, and the density is 0.96g / cm 3 The diameter of the fiber is 0.3 mm and the tensile strength is 510 MPa; the boron mud is alkaline with a pH value of 8-10; the biological enzyme is Tairan enzyme purchased from Nature Plus, Inc. of the United States; carboxymethyl chitosan was purchased from Shanghai Yuanye Biotechnology Co., Ltd. with CAS number 83512-85-0, item number S30948, and the degree of carboxylation ≥80%.
[0039] Example 1
[0040] This embodiment discloses a method for solidifying shield waste clay and preparing the same. Figure 1 As shown, the following steps are included:
[0041] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 60 parts of magnesium oxide, 70 parts of carbide slag and 70 parts of boron mud and mixing them evenly to obtain a mixture A;
[0042] (2) mixing 4 parts of modified sisal fiber, 6.5 parts of bioenzyme-attapulgite and 2.5 parts of anionic surfactant to obtain a composite additive;
[0043] (3) Mixing mixture A and 13 parts of the composite additive uniformly to obtain mixture B;
[0044] (4) Add 2.5 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0045] Wherein, the preparation method of modified sisal fiber is as follows:
[0046] A1. Cut 10 g of sisal fiber into short fibers of 2-3 cm in length, place them in 400 mL of deionized water for ultrasonic cleaning, and ultrasonically clean them at 40° C. for 30 min; then immerse 10 g of sisal fiber in 200 mL of 8% by mass NaOH solution for alkali treatment, soak for 2.5 h, repeatedly rinse with deionized water until neutral, and dry at 60° C. for 12 h to obtain pretreated sisal fiber;
[0047] A2. Mix 10g of pretreated sisal fiber with 100mL of deionized water, add 0.8g of maleic anhydride, add 0.15g of ammonium persulfate and 0.08g of anhydrous sodium sulfite under nitrogen protection, react at 90°C for 3h, and after the reaction, cool the mixture to room temperature. Filter the reaction product, rinse it with deionized water 3 times, acid wash to remove unreacted maleic anhydride, rinse it with deionized water again until neutral, vacuum dry it at 60°C for 12h, grind the dried modified sisal fiber, and pass it through a 100-mesh sieve to obtain modified sisal fiber.
[0048] The preparation method of bio-enzyme-attapulgite is as follows:
[0049] S1. Soak 10 g of attapulgite in 100 mL of 0.5 M hydrochloric acid solution, and activate the reaction at 75 ° C for 3 h. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0050] S2, 10g of pretreated attapulgite was placed in 100mL of ethanol aqueous solution, and after ultrasonic dispersion for 30min, it was added into 100mL of modification solution (3.5% by mass of γ-aminopropyltriethoxysilane solution, the solvent was ethanol) and immersed, and stirred at 55°C for 3h. After the reaction, the solid was separated by centrifugation (4000rpm, 10min), washed with ethanol 3 times, vacuum dried at 60°C for 12h, and ground and sieved through a 200-mesh sieve to obtain surface-modified attapulgite;
[0051] S3. Disperse 10 g of surface modified attapulgite in 100 mL of 1.3% bio-enzyme solution, adsorb at 8 °C for 14 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 1 g of carboxymethyl chitosan and 1 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly, let stand for 45 min, and then freeze-dry at 4 °C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0052] Example 2
[0053] This embodiment discloses a solidified shield waste clay and a preparation method thereof, comprising the following steps:
[0054] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 20 parts of magnesium oxide, 40 parts of carbide slag and 60 parts of boron mud and mixing them evenly to obtain a mixture A;
[0055] (2) mixing 3 parts of modified sisal fiber, 5 parts of bio-enzyme-attapulgite and 2 parts of anionic surfactant to obtain a composite additive;
[0056] (3) Mixing mixture A and 10 parts of the composite additive uniformly to obtain mixture B;
[0057] (4) Add 2 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0058] Wherein, the preparation method of modified sisal fiber is as follows:
[0059] A1. Cut 10 g of sisal fiber into short fibers of 2-3 cm in length, place them in 400 mL of deionized water for ultrasonic cleaning, and ultrasonically clean them at 40° C. for 30 min; then immerse 10 g of sisal fiber in 200 mL of 5% by mass NaOH solution for alkali treatment, soak for 3 h, repeatedly rinse with deionized water until neutral, and dry at 60° C. for 12 h to obtain pretreated sisal fiber;
[0060] A2. Mix 10g of pretreated sisal fiber with 100mL of deionized water, add 0.5g of maleic anhydride, add 0.1g of ammonium persulfate and 0.05g of anhydrous sodium sulfite under nitrogen protection, react at 80°C for 3.5h, and after the reaction, cool the mixture to room temperature. Filter the reaction product, rinse it with deionized water three times, acid wash to remove unreacted maleic anhydride, rinse it with deionized water again until neutral, vacuum dry it at 60°C for 12h, grind the dried modified sisal fiber, and pass it through a 100-mesh sieve to obtain modified sisal fiber.
[0061] The preparation method of biological enzyme-attapulgite is as follows:
[0062] S1. Soak 10 g of attapulgite in 100 mL of 0.1 M hydrochloric acid solution, and activate the reaction at 90 ° C for 2 h. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0063] S2, 10g of pretreated attapulgite was placed in 100mL of ethanol aqueous solution, and after ultrasonic dispersion for 30min, it was added into 100mL of modification liquid (2% by mass of γ-aminopropyltriethoxysilane solution, the solvent was ethanol) and soaked, and stirred at 50°C for 4h. After the reaction, the solid was separated by centrifugation (4000rpm, 10min), washed with ethanol 3 times, vacuum dried at 60°C for 12h, and passed through a 200-mesh sieve after grinding to obtain surface-modified attapulgite;
[0064] S3. Disperse 10 g of surface modified attapulgite in 100 mL of 0.5% bio-enzyme solution, adsorb at 10°C for 12 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 0.5 g of carboxymethyl chitosan and 0.5 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly and let stand for 30 min, then freeze-dry at 4°C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0065] Example 3
[0066] This embodiment discloses a solidified shield waste clay and a preparation method thereof, comprising the following steps:
[0067] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 80 parts of magnesium oxide, 100 parts of carbide slag and 80 parts of boron mud and mixing them evenly to obtain a mixture A;
[0068] (2) mixing 5 parts of modified sisal fiber, 8 parts of bio-enzyme-attapulgite and 3 parts of anionic surfactant to obtain a composite additive;
[0069] (3) Mixing mixture A and 15 parts of the composite additive uniformly to obtain mixture B;
[0070] (4) Add 3 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0071] Wherein, the preparation method of modified sisal fiber is as follows:
[0072] A1. Cut 10 g of sisal fiber into short fibers of 2-3 cm in length, place them in 400 mL of deionized water for ultrasonic cleaning, and ultrasonically clean them at 40° C. for 30 min; then immerse 10 g of sisal fiber in 200 mL of 10% by mass NaOH solution for alkali treatment, soak for 2 h, repeatedly rinse with deionized water until neutral, and dry at 60° C. for 12 h to obtain pretreated sisal fiber;
[0073] A2. Mix 10g of pretreated sisal fiber with 100mL of deionized water, add 1g of maleic anhydride, add 0.2g of ammonium persulfate and 0.1g of anhydrous sodium sulfite under nitrogen protection, react at 100°C for 2.5h, and after the reaction, cool the mixture to room temperature. Filter the reaction product, rinse it with deionized water three times, acid wash to remove unreacted maleic anhydride, rinse it with deionized water again until neutral, vacuum dry it at 60°C for 12h, grind the dried modified sisal fiber, and pass it through a 100-mesh sieve to obtain modified sisal fiber.
[0074] The preparation method of biological enzyme-attapulgite is as follows:
[0075] S1. Soak 10 g of attapulgite in 100 mL of 1.0 M hydrochloric acid solution, and activate the reaction at 60 ° C for 4 hours. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 hours, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0076] S2, 10g of pretreated attapulgite was placed in 100mL of ethanol aqueous solution, and after ultrasonic dispersion for 30min, it was added into 100mL of modification liquid (5% by mass of γ-aminopropyltriethoxysilane solution, the solvent was ethanol) and immersed, and stirred at 60°C for 2h. After the reaction, the solid was separated by centrifugation (4000rpm, 10min), washed with ethanol 3 times, vacuum dried at 60°C for 12h, and passed through a 200-mesh sieve after grinding to obtain surface-modified attapulgite;
[0077] S3. Disperse 10 g of surface modified attapulgite in 100 mL of 2% bio-enzyme solution, adsorb at 4 °C for 16 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 1.5 g of carboxymethyl chitosan and 1.5 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly, let stand for 60 min, and then freeze-dry at 4 °C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0078] Example 4
[0079] This embodiment discloses a solidified shield waste clay and a preparation method thereof, comprising the following steps:
[0080] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 40 parts of magnesium oxide, 60 parts of carbide slag and 70 parts of boron mud and mixing them evenly to obtain a mixture A;
[0081] (2) mixing 3.5 parts of modified sisal fiber, 7 parts of bioenzyme-attapulgite and 2.5 parts of anionic surfactant to obtain a composite additive;
[0082] (3) Mixing mixture A and 11 parts of the composite additive uniformly to obtain mixture B;
[0083] (4) Add 2.5 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0084] Wherein, the preparation method of modified sisal fiber is as follows:
[0085] A1. Cut 10 g of sisal fiber into short fibers of 2-3 cm in length, place them in 400 mL of deionized water for ultrasonic cleaning, and ultrasonically clean them at 40° C. for 30 min; then immerse 10 g of sisal fiber in 200 mL of 7% by mass NaOH solution for alkali treatment, soak for 2.5 h, repeatedly rinse with deionized water until neutral, and dry at 60° C. for 12 h to obtain pretreated sisal fiber;
[0086] A2. Mix 10g of pretreated sisal fiber with 100mL of deionized water, add 0.6g of maleic anhydride, add 0.12g of ammonium persulfate and 0.07g of anhydrous sodium sulfite under nitrogen protection, react at 90°C for 3h, and after the reaction, cool the mixture to room temperature. Filter the reaction product, rinse it with deionized water 3 times, acid wash to remove unreacted maleic anhydride, rinse it with deionized water again until neutral, vacuum dry it at 60°C for 12h, grind the dried modified sisal fiber, and pass it through a 100-mesh sieve to obtain modified sisal fiber.
[0087] The preparation method of biological enzyme-attapulgite is as follows:
[0088] S1. Soak 10 g of attapulgite in 100 mL of 0.8 M hydrochloric acid solution, and activate the reaction at 70 ° C for 3 h. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0089] S2, 10g of pretreated attapulgite was placed in 100mL of ethanol aqueous solution, and after ultrasonic dispersion for 30min, it was added into 100mL of modified solution (4% by mass of γ-aminopropyltriethoxysilane solution, the solvent was ethanol) and immersed, and stirred at 55°C for 3h. After the reaction, the solid was separated by centrifugation (4000rpm, 10min), washed with ethanol 3 times, vacuum dried at 60°C for 12h, and ground and sieved through a 200-mesh sieve to obtain surface-modified attapulgite;
[0090] S3. Disperse 10 g of surface modified attapulgite in 100 mL of 1% bio-enzyme solution, adsorb at 9 ° C for 13 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 1.2 g of carboxymethyl chitosan and 1.2 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly, let stand for 40 min, and then freeze-dry at 4 ° C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0091] Comparative Example 1
[0092] This embodiment discloses a solidified shield waste clay and a preparation method thereof, comprising the following steps:
[0093] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 60 parts of magnesium oxide, 70 parts of carbide slag and 70 parts of boron mud and mixing them evenly to obtain a mixture A;
[0094] (2) mixing 4 parts of sisal fiber, 6.5 parts of bio-enzyme-attapulgite and 2.5 parts of anionic surfactant to obtain a composite additive;
[0095] (3) Mixing mixture A and 13 parts of the composite additive uniformly to obtain mixture B;
[0096] (4) Add 2.5 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0097] The preparation method of biological enzyme-attapulgite is as follows:
[0098] S1. Soak 10 g of attapulgite in 100 mL of 0.5 M hydrochloric acid solution, and activate the reaction at 75 ° C for 3 h. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0099] S2, 10g of pretreated attapulgite was placed in 100mL of ethanol aqueous solution, and after ultrasonic dispersion for 30min, it was added into 100mL of modification solution (3.5% by mass of γ-aminopropyltriethoxysilane solution, the solvent was ethanol) and immersed, and stirred at 55°C for 3h. After the reaction, the solid was separated by centrifugation (4000rpm, 10min), washed with ethanol 3 times, vacuum dried at 60°C for 12h, and ground and sieved through a 200-mesh sieve to obtain surface-modified attapulgite;
[0100] S3. Disperse 10 g of surface modified attapulgite in 100 mL of 1.3% bio-enzyme solution, adsorb at 8 °C for 14 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 1 g of carboxymethyl chitosan and 1 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly, let stand for 45 min, and then freeze-dry at 4 °C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0101] Comparative Example 2
[0102] This embodiment discloses a solidified shield waste clay and a preparation method thereof, comprising the following steps:
[0103] (1) crushing and sieving the waste clay to less than 2 mm, then weighing 1000 parts of the waste clay powder, 60 parts of magnesium oxide, 70 parts of carbide slag and 70 parts of boron mud and mixing them evenly to obtain a mixture A;
[0104] (2) mixing 4 parts of modified sisal fiber, 6.5 parts of bio-enzyme-attapulgite and 2.5 parts of anionic surfactant to obtain a composite additive;
[0105] (3) Mixing mixture A and 13 parts of the composite additive uniformly to obtain mixture B;
[0106] (4) Add 2.5 parts of sodium bicarbonate to mixture B and stir evenly to obtain solidified shield waste clay.
[0107] Wherein, the preparation method of modified sisal fiber is as follows:
[0108] A1. Cut 10 g of sisal fiber into short fibers of 2-3 cm in length, place them in 400 mL of deionized water for ultrasonic cleaning, and ultrasonically clean them at 40° C. for 30 min; then immerse 10 g of sisal fiber in 200 mL of 8% by mass NaOH solution for alkali treatment, soak for 2.5 h, repeatedly rinse with deionized water until neutral, and dry at 60° C. for 12 h to obtain pretreated sisal fiber;
[0109] A2. Mix 10g of pretreated sisal fiber with 100mL of deionized water, add 0.8g of maleic anhydride, add 0.15g of ammonium persulfate and 0.08g of anhydrous sodium sulfite under nitrogen protection, react at 90°C for 3h, and after the reaction, cool the mixture to room temperature. Filter the reaction product, rinse it with deionized water 3 times, acid wash to remove unreacted maleic anhydride, rinse it with deionized water again until neutral, vacuum dry it at 60°C for 12h, grind the dried modified sisal fiber, and pass it through a 100-mesh sieve to obtain modified sisal fiber.
[0110] The preparation method of bio-enzyme-attapulgite is as follows:
[0111] S1. Soak 10 g of attapulgite in 100 mL of 0.5 M hydrochloric acid solution, and activate the reaction at 75 ° C for 3 h. After the reaction, cool the mixture to room temperature, centrifuge to separate the solid (4000 rpm, 10 min), wash with deionized water until neutral, dry at 60 ° C for 12 h, grind and pass through a 200 mesh sieve to obtain pretreated attapulgite;
[0112] S3. Disperse 10 g of pretreated attapulgite in 100 mL of 1.3% bio-enzyme solution, adsorb at 8 ° C for 14 h, and centrifuge to separate the solid after the adsorption to obtain bio-enzyme-loaded attapulgite; dissolve 1 g of carboxymethyl chitosan and 1 g of gelatin in 50 mL of deionized water, and then add 10 g of bio-enzyme-loaded attapulgite to the above mixed solution, stir evenly and let stand for 45 min, then freeze-dry at 4 ° C for 24 h, grind, and pass through a 200-mesh sieve to obtain bio-enzyme-attapulgite.
[0113] Performance Testing
[0114] Pour the solidified shield waste clay prepared in the embodiment and the comparative example into the mold, vibrate with a vibrating table to ensure that the material is evenly distributed and free of bubbles, place the mold in a constant temperature and humidity curing box, control the temperature at 20±2°C, and keep the relative humidity above 95% for initial curing for 24-48h. After demoulding, place the sample in a carbonization curing box, control the temperature at 20±2°C, the relative humidity at 60-70%, and introduce CO2 gas with a concentration of 20-30% for carbonization curing, and the carbonization time is 2h and 4h; then transfer the sample to a standard curing room for curing, the temperature is 20±2°C, the relative humidity is above 95%, and the curing time is 7d. The compressive strength and water stability of 7 days were tested, wherein the compressive strength was tested with reference to GB / T16925-1997, and the water stability test method was as follows: the solidified shield waste clay (cured for 7 days) prepared in the embodiment and the comparative example, and the compacted plain soil specimens of the same size as the product were immersed in water at room temperature for a total of 12 hours, and then the specimens were taken out and naturally air-dried for 12 hours, and the test was repeated 5 times, and the compressive strength of the specimens after immersion in water was tested.
[0115]
[0116] As can be seen from Table 1, the compressive strength and water stability of the solidified shield waste clay prepared by the present invention meet the requirements of the secondary highway base layer engineering fill. With the help of the above technical solution of the present invention, a reasonable curing agent formula can be used to solidify the solidified soil with high compressive strength and good water stability. Compared with the existing method for treating waste soil, the present invention makes full use of the waste soil, can effectively save resources and costs, reduce environmental pollution, and can prepare a highway base fill that meets the requirements of strength and stability.
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for solidifying shield waste clay, characterized in that: The invention comprises the following components by weight: 1000 parts of waste clay, 20-80 parts of magnesium oxide, 40-100 parts of carbide slag, 60-80 parts of boron mud, 10-15 parts of composite additives and 2-3 parts of activator, wherein the composite additives are formed by compounding modified sisal fiber, biological enzyme-attapulgite and anionic surfactant.
2. The solidified shield waste clay according to claim 1, characterized in that: The composite additive comprises 3-5 parts of modified sisal fiber, 5-8 parts of biological enzyme-attapulgite, and 2-3 parts of anionic surfactant.
3. The solidified shield waste clay according to claim 1, characterized in that: The preparation method of the modified sisal fiber comprises the following steps: A1, placing the sisal fiber in deionized water for ultrasonic cleaning, and then immersing the sisal fiber in a NaOH solution for alkali treatment to obtain pretreated sisal fiber; A2. The pretreated sisal fiber is mixed with deionized water, maleic anhydride is added, and then ammonium persulfate and anhydrous sodium sulfite are added, and the mixture is reacted at 80-100° C. for 2.5-3.5 hours to obtain modified sisal fiber.
4. The solidified shield waste clay according to claim 3, characterized in that: In step A1, the mass percentage of the NaOH solution is 5-10%, and the alkali treatment time is 2-3 hours.
5. The solidified shield waste clay according to claim 3, characterized in that: In step A2, the mass ratio of the pretreated sisal fiber, maleic anhydride, ammonium persulfate and anhydrous sodium sulfite is 100:5-10:1-2:0.5-1.
6. The solidified shield waste clay according to claim 1, characterized in that: The preparation method of the biological enzyme-attapulgite comprises the following steps: S1, soaking the attapulgite in a 0.1-1.0 M hydrochloric acid solution, and activating the reaction at 60-90° C. for 2-4 hours to obtain pretreated attapulgite; S2, placing the pretreated attapulgite in an ethanol aqueous solution, adding the modified solution to soak, stirring and reacting at 50-60° C. for 2-4 hours to obtain surface-modified attapulgite; S3. Disperse the surface modified attapulgite in the biological enzyme solution, adsorb it at 4-10°C for 12-16 hours to obtain the attapulgite loaded with biological enzymes, and then mix the attapulgite loaded with biological enzymes with carboxymethyl chitosan and gelatin, and let it stand for 30-60 minutes to obtain biological enzyme-attapulgite.
7. The solidified shield waste clay according to claim 6, characterized in that: In step S2, the modifying liquid is one or more of γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane and γ-aminopropyltrimethoxysilane, and the concentration of the modifying liquid is 2-5%.
8. The solidified shield waste clay according to claim 6, characterized in that: In step S3, the concentration of the bio-enzyme solution is 0.5-2%, and the mass ratio of attapulgite, carboxymethyl chitosan and gelatin loaded with the bio-enzyme is 100:(5-15):(5-15).
9. The solidified shield waste clay according to claim 1, characterized in that: The activator is sodium bicarbonate or citric acid, and the anionic surfactant is fatty alcohol polyoxyethylene ether sodium sulfate and / or sodium lauryl sulfate.
10. A method for preparing solidified shield waste clay according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) crushing and sieving the waste clay to less than 2 mm, and then mixing the waste clay powder, magnesium oxide, carbide slag and boron mud to obtain a mixture A; (2) mixing the modified sisal fiber, the bio-enzyme-attapulgite and the anionic surfactant to obtain a composite additive; (3) uniformly mixing the mixture A and the composite additive to obtain a mixture B; (4) Add an activator to mixture B and stir evenly to obtain solidified shield waste clay.
Citation Information
Patent Citations
An inorganic composite curing agent suitable for soil in coastal areas and its preparation method
CN111116153B